PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS ZEPETO DAN WINK PADA MATERI PENGUKURAN DAN VOLUME KELAS IV SDN DUKUH KUPANG V SURABAYA - Vebriani, Veronika; Jarmani; Friendha Yuanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop Zepeto and Wink-based video learning media on measurement and volume for fourth-grade students at SDN Dukuh Kupang V Surabaya. The background of this study is based on students' low understanding of abstract measurement and volume concepts and the limitations of conventional learning media. This study uses the Research and Development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of fourth-grade students. Data collection techniques included observation, interviews, questionnaires validated by media and subject matter experts, as well as pretest and posttest to measure the effectiveness of the learning media. The data obtained were analyzed descriptively, quantitatively, and qualitatively.